Host species and temperature drive beech and Scots pine phyllosphere microbiota across European forests - Sangiorgio, Daniela; Cáliz, Joan; Mattana, Stefania; Barceló, Anna; De Cinti, Bruno; Elustondo, David; Hellsten, Sofie; Magnani, Federico; Matteucci, Giorgio; Merilä, Päivi; Nicolas, Manuel; Ravaioli, Dario; et al. (Springer Nature, 2024)
Tree-microbe interactions are essential for forest ecosystem functioning. Most plant–microbe research has focused on the rhizosphere, while composition of microbial communities in the phyllosphere remains underexplored. Here, we use 16S rRNA gene sequencing to explore differences between beech and Scots pine phyllospheric microbiomes at the European continental scale, map their functional profiles, and elucidate the role of host trees, forest features, and environmental factors such as climate and atmospheric deposition in phyllosphere microbiota assembly. We identified tree species and the associated foliar trait (specifically carbon:nitrogen ratio) as primary drivers of the bacterial communities. We characterized taxonomical and functional composition of epiphytic bacteria in the phyllosphere of beech and Scots pine across an environmental gradient from Fennoscandia to the Mediterranean area, with major changes in temperature and nitrogen deposition. We also showed that temperature and nitrogen deposition played a crucial role in affecting their assembly for both tree species. This study contributes to advancing our understanding on factors shaping phyllosphere microbial communities in beech and Scots pine at the European continental scale, highlighting the need of broad-scale comparative studies (covering a wide range of foliar traits and environmental conditions) to elucidate how phyllosphere microbiota mediates ecosystem responses to global change.
Keywords: tree-microbe interactions; phyllospheric microbiomes